Degradation Factors on Marine Fisheries in The Coastline of Dernah, East of Libya (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
This study has been conducted in the period between 2016 and 2019 on along the Derna coast. Severe decline has occurred in the case of marine fisheries in the area, where the Region was subjected to many pressures and crises, such as the subsequent closure of the fishing season due to war conditions and the widespread use of explosives in fishing (recording 896 accidents during the study period). The entry of foreign fishermen into the maritime fisheries sector without a license has resulted in a loss of productivity. The entry of foreign fishermen into the maritime fisheries sector without a license has resulted in a loss of productivity . The entry of foreign fishermen into the maritime fisheries sector without a license has resulted in a loss of productivity. The area reported a production of 5943 kilograms of fish in 2019 and decreased volume production from in 2015(25950 kilograms). and a significant decline in the number of fishing boats along the Derna coastline in the fishing sector. Decline from 200 different boats in 2015 to just 67 in 2019, and a significant decline in the number of fishing boats along the Derna coastline in the fishing sector from 200 different boats in 2015 to just 67 in 2019. resulting in very high fish and crustacean prices and a large number of local Fishers for other, more profitable occupations. In this study 83 native fish species, 4 endemic to the Mediterranean Sea, 20 non-indigenous of Lessepsian origin and 2 range expanding taxa from Gibraltar were recorded.
Keywords: Marine fisheries; degradation; Derna coast; eastern coast; Mediterranean Sea; Libya